Formative assessment in teacher talk during lesson studies. Issue 4 (10th October 2016) - van Halem, Nicolette; Goei, Sui Lin; Akkerman, Sanne F.
Abstract : Purpose: The purpose of this paper is to evaluate the extent of systematic examination of students' educational (support) needs by teachers participating in lesson study (LS) meetings within a framework of formative assessment (FA). Design/methodology/approach: The study took place in the context of upper preparatory vocational education in the Netherlands. The learning trajectory of two LS teams was examined qualitatively, using the framework of FA to analyze teachers' explorative talk during LS-meetings. The sample included Dutch language teachers and mathematics teachers. Findings: Findings revealed how the process of FA was intertwined with the LS process. Systematic examination of teaching practice was partly identified, however, FA was frequently inadequately applied. Teachers tended to rush into talk about pedagogics, instead of identification of goals and students' educational (support) needs. In total, 12 characteristics of teacher talk were related to the extent to which FA was applied. Research limitations/implications: The findings of this study suggest that guidance and support during LS-meetings is desirable for systematic practices during LS-meetings and this guidance and support should adapt to specific weaknesses and strengths of a LS team. Originality/value: This study builds on previous findings suggesting that a systematic approach is important for teachers during LS-meetings. The findings provide a starting point for realizing the potential of LS in preparatory vocational education, by revealing potential pitfalls of systematic practice during LS-meetings. Moreover, this study presents a framework of FA as a potential tool in facilitating a systematic practice of LS.